Sensitive Troponin I Assay in Early Diagnosis of Acute Myocardial Infarction - Keller, Till; Zeller, Tanja; Peetz, Dirk; Tzikas, Stergios; Roth, Alexander; Czyz, Ewa; Bickel, Christoph; Baldus, Stephan; Warnholtz, Ascan; Fröhlich, Meike; Sinning, Christoph R; Eleftheriadis, Medea S; et al. (The New England journal of medicine, 2009)
A highly sensitive assay for troponin I was found to improve on standard serum markers for the diagnosis of acute myocardial infarction. The measurement of troponin I even within 3 hours after the onset of chest pain provided useful diagnostic information. A highly sensitive assay for troponin I was found to improve on standard serum markers for the diagnosis of acute myocardial infarction. The measurement of troponin I even within 3 hours after the onset of chest pain provided useful diagnostic information. An early diagnosis of myocardial infarction facilitates rapid decision making and treatment and therefore improves the outcome in patients presenting with symptoms of chest pain. 1 , 2 The introduction of the testing of necrosis markers in the emergency setting constituted a milestone in the care of patients with chest pain. 3 – 6 Guidelines recommend the measurement of cardiac troponin levels for the diagnosis of myocardial infarction, with a level above the 99th percentile in a reference population as the discriminatory value, including the detection of a rise or fall in the troponin levels. 7 – 9 Although conventional necrosis markers have a high diagnostic . . .